Pengaruh Kedisiplinan Belajar dan Moral Siswa Terhadap Prestasi Belajar Pendidikan Agama Islam - Maratus Sholikhah, Siti; Mujiburrohman; Nurhidayati, Indah (Universitas Majalengka, 2023)
This study reviews how students' learning discipline and morals contribute to learning achievement in Islamic religious education, with a focus on the school environment. This study aims to: 1) determine the effect of learning discipline on learning achievement in Islamic Religious Education; 2) determine the effect of student morals on learning achievement in Islamic Religious Education; 3) determine the effect of discipline and student morals on learning achievement in Islamic Religious Education. The research method used was quantitative-correlational by involving a sample of students from SMP Muhammadiyah 4 Balen, Bojonegoro Regency. Data were collected through questionnaires and statistical analysis was conducted to evaluate the relationship between the variables of learning discipline, student morale, and learning achievement. The results of this study explain that: 1) learning discipline does not have a significant influence on student learning achievement in Islamic religious education subjects; 2) there is a significant influence between student morale on learning achievement in Islamic religious education subjects; 3) learning discipline and student morale together have a significant influence on learning achievement.